2019
DOI: 10.1002/adfm.201907840
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Plasmonic Absorption Losses at Rear Electrodes in High‐Efficiency Silicon Solar Cells Using Dopant‐Free Contact Stacks

Abstract: Although charge-carrier selectivity in conventional crystalline silicon (c-Si) solar cells is usually realized by doping Si, the presence of dopants imposes inherent performance limitations due to parasitic absorption and carrier recombination. The development of alternative carrier-selective contacts, using non-Si electron and hole transport layers, has the potential to overcome such drawbacks and simultaneously reduce the cost and/or simplify the fabrication process of c-Si solar cells. Nevertheless, devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 37 publications
0
86
0
Order By: Relevance
“…After inserting the ITO layer, the parasitic aborption of Ag ( Figure S3b, Supporting Information) and MoO X ( Figure S3c, Supporting Information) in the wavelength range of 1030-1100 nm are depressed, while an additional absorption from ITO layer ( Figure S3d, Supporting Information) is seen due to its free carrier absorption in the infrared range. [7] The absorptions of both SiO X and V 2 O X are below 5 × 10 −14 % because of their low extinction coefficient. [59,60] The equivalent current density (J eq ) in bulk Si and each individual functional layer at rear side with diffferent contact configurations are further quantitatively evaluated.…”
Section: (6 Of 9)mentioning
confidence: 99%
See 1 more Smart Citation
“…After inserting the ITO layer, the parasitic aborption of Ag ( Figure S3b, Supporting Information) and MoO X ( Figure S3c, Supporting Information) in the wavelength range of 1030-1100 nm are depressed, while an additional absorption from ITO layer ( Figure S3d, Supporting Information) is seen due to its free carrier absorption in the infrared range. [7] The absorptions of both SiO X and V 2 O X are below 5 × 10 −14 % because of their low extinction coefficient. [59,60] The equivalent current density (J eq ) in bulk Si and each individual functional layer at rear side with diffferent contact configurations are further quantitatively evaluated.…”
Section: (6 Of 9)mentioning
confidence: 99%
“…[5] The HIT solar cells also suffer a high parasitic absorption arising from the a-Si:H and transparent conductive oxide (TCO) layers. [6,7] With the aim of further boosting the efficiency with a lower cost, a variety of transition metal compounds have been adopted as carrier-selective contacts (CSCs) for c-Si heterojunction solar cells. The transition metal oxides (TMOs) with large work functions (>5.5 eV), such as MoO X , [8][9][10][11] [12][13][14][15] and WO X, [16][17][18] can induce an accumulation of holes in p-type silicon (p-Si) [8] or depletion of electrons in n-type silicon (n-Si), [19] thus benefiting the hole transport.…”
mentioning
confidence: 99%
“…This formation may cause a trapping layer, leading to increased D it and other effects. However, as shown recently, it is also possible that SiO x is forming at the interface without a significant detrimental effect on passivation [62]. In fact, Nayak et al reported that an intentionally introduced SiO x layer actually improves the solar cell performance in (n) c-Si / (i) SiO x / (p) NiO x devices [22].…”
Section: B Case Study: Sputtered P-type Nio X As a Hole-selective Comentioning
confidence: 96%
“…25 Moreover, with well-designed transparent electrodes (usually transparent conductive oxides, TCOs) at their front and rear, SHJ cells feature high external quantum efficiencies (EQEs) for long-wavelength photons, thanks to their displaced-metal rear contact structure and the possibility to employ dopant-free junctions. 26 For these reasons, they may be regarded as ideal bottom cell partner in silicon-based tandems, 27 and have indeed been employed for most high-efficiency perovskite/ silicon tandems to date. According to the polarity of the tandem, these silicon films can -at least in principle -be coupled either as Si(n + ) with the perovskite HTL or as Si(p + ) with the perovskite ETL, resulting respectively in Si(n + )/HTL and Si(p + )/ETL hybrid RJs.…”
Section: Basic Properties Of Tunneling Junctionsmentioning
confidence: 99%